Kewajiban Pemerintah atas Hak Imbalan Jasa Pelayanan Kesehatan Dokter Internsip - Dzulqarnain Andira; Mokhamad Kohoirul Huda; Sulaksono - (Universitas Merdeka Madiun, 2021)
This Study analyzed the government obligation for the rights of medical service reward for internship doctor at wahana internsip. The aim of this research is to know the status of an internship doctor in accordance with statutory regulations, as well as the government's responsibility for medical service reward of an internship doctor at wahana internsip. The absence of laws and regulations that regulate the rights of an internship doctor regarding compensation or reward for services from medical services performed at wahana internsip or a place where the internship doctor is in charge of providing health services. The approachment method of this research is statutory, conceptual, and comparative. The collecting method for legal materials is done by editing, classifying, and organizing. The data analysis was done qualitively. The result of this study is the status of internship doctor is a doctor that already has competencies as a medical practitioner that has been approved by Indonesian Doctor Colegium (KDI), and the intern has full responsibility for medical service at the internship place. The Government is responsible for medical service reward of internship doctor.